Effectiveness of health belief model-based prenatal education on anemia prevention behaviors among pregnant women: A systematic review - Araujo, Febriana Soares De; Susanto, Herry; Wahyuni, Sri (Lentera Perawat, 2026)
Background: Anemia during pregnancy remains a major public health concern because it contributes to adverse maternal and fetal outcomes and is strongly influenced by modifiable health behaviors. Prenatal education grounded in behavioral theory has gained increasing attention as a strategy to improve preventive practices, particularly in primary care and community settings. The Health Belief Model offers a relevant framework because it addresses women’s perceptions of risk, benefits, barriers, and cues to action related to anemia prevention. Objective: This systematic review aimed to evaluate the effectiveness of Health Belief Model-based prenatal education on anemia prevention behaviors among pregnant women in community health centers and other primary care settings. Methods: This study applied a systematic review design. Literature searches were conducted across major electronic databases using combinations of terms related to the Health Belief Model, prenatal education, pregnant women, anemia, iron supplementation, hemoglobin, and primary health care. The main outcomes were hemoglobin level, anemia prevalence, iron-folic acid supplementation adherence, dietary intake, and behavioral determinants. Data were extracted using a structured form and synthesized narratively. Results: Eight studies were included in the final synthesis. The findings consistently showed that Health Belief Model-based or theory-based prenatal education improved anemia prevention behaviors and related health outcomes. The strongest effects were observed in iron-folic acid supplementation adherence, hemoglobin improvement, anemia reduction, and healthier dietary practices. Several studies also reported gains in maternal knowledge, attitudes, and selected Health Belief Model constructs, especially perceived susceptibility and cues to action. Interventions that combined counseling with educational media, reminder systems, or repeated follow-up produced more consistent benefits across settings. Conclusion: Health Belief Model-based prenatal education appears to be an effective strategy for improving anemia prevention behaviors among pregnant women in community and primary care settings. Integrating theory-based educational interventions into routine antenatal services may strengthen maternal anemia prevention and support better pregnancy outcomes.